Thermal Uniformity Analysis of Polar and Non-polar Solvents During Heating Based on Numerical Calculation - Liu, Jian-Yi; Bai, Yang; Luo, Ping-Ya; Wang, Ping-Quan; Shu, Jun (Asian Journal of Chemistry, 2013)
It is a key issue to obtain uniform heating in certain regions of an applicator. In this paper, the non-polar (CCl4) and polar (water) solvents are heated together in same container. The silicon-carbide is chose to be a vessel. The uniformities of temperature were analyzed using finite-element method under different configurations during heating. The results show that the temperature uniformity is influenced by solvent volume size and volume ratio and the thermal energy transfers from the non-polar to polar solvent for temperature difference. When the improvement in temperature uniformity is not obvious, it can improve significantly the uniformity of temperature by changing the volume or volume ratio.